Analysis of the Implementation of the FLIP Application for Bank Account Transfers Using the UTAUT2 Method - Lestari, Nanik; Ananda Putri Amia, Rizqi (Pusat P2M Politeknik Negeri Batam, 2026)
This investigation delves into the determinants shaping Flip's adoption, a complimentary interbank transfer application, by students at Batam State Polytechnic. The inquiry utilized primary data, gathered via an online survey from 108 participants. A comprehensive set of eleven variables underwent scrutiny: Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, Price Value, Habit, Perceived Risk, Perceived Trust, Self-Efficacy, Intention to Use, and Use Behavior. Data processing relied on Partial Least Squares Structural Equation Modeling (PLS-SEM), facilitated by SmartPLS 4 software. The outer model assessment validated that all conceptual constructs satisfied stringent criteria for validity and reliability. Examining the inner model revealed robust predictive accuracy, with R² values registering 0.787 for Intention to Use and 0.729 for Use Behavior. From the eleven hypotheses put to the test, four garnered empirical support: Hedonic Motivation, Habit, and Self-Efficacy demonstrated a pronounced effect on Intention to Use, while Habit also exerted a substantial influence on Use Behavior. These outcomes suggest that internal psychological drivers—such as motivation, ingrained routines, and personal assurance—are more pivotal in influencing technology acceptance than external elements like anticipated performance, perceived effort, peer influence, or cost considerations. Consequently, these findings imply that developers should prioritize refining the user experience, cultivating user confidence, and fostering habitual engagement to bolster the uptake of digital financial technologies, particularly within the student demographic.